Trapping two types of Rayleigh particles simultaneously by a focused rotational elliptical Laguerre–Gaussian correlated Schell-model beam. (March 2021) - Yang, Bo; Chen, Yahong; Wang, Fei; Cai, Yangjian
Highlights: Spatial coherence structure of a partially coherent light beam can be used as a novel tool for the manipulation of optical radiation force. The symmetry of trapping area can be modulated by the symmetry of the spatial coherence structure of the incident light beam. Two types of Rayleigh dielectric particles of different refractive indices can be trapped simultaneously by a focused rotational elliptical Laguerre–Gaussian correlated Schell-model beam. The effects of beam order and spatial coherence widths on the radiation forces are analyzed in detail. Abstract: We analyze the optical radiation forces, produced by a focused rotational elliptical Laguerre–Gaussian correlated Schell-model (ELGSM) beam, on the dielectric particles of different refractive indices in the Rayleigh scattering regime. It is found that through a judicious modulation of the initial spatial coherence width and the beam order of the correlation function of the rotational ELGSM beam, the particles with higher refractive index (compared with the ambient) can be trapped along an elliptical ring centered at the focus, the particles with lower refractive index, at the same time, will be trapped at the focal point. Our results also show that the trapping area/range can be modulated by structuring the correlation function of the beam. By comparing the gradient, scattering, Brownian, and gravity forces acting on the particles, the trapping stability is analyzed. Our results indicate that the coherence structure engineering can be used as an alternative approach to modulate the symmetry of the optical trapping area.